THE EFFECT OF ADOPTION OF INNOVATION ON THE PERFORMANCE OF MICRO AND SMALL ENTREPRISES OF DRIED FISH PROCESSING IN BENGKULU CITY - January Rizki; Heni K Suwarsinah; Wahyu Budi Priatna (Jurnal Manajemen & Agribisnis, 2019)
This research aimed to analyze the influence of the characteristics of innovation, internal and external factors to the adoption of innovation and analyze the influence adoption of innovation on the performance of small micro enterprises (MSEs) processing of dried fish in the city of Bengkulu. The influence of the adoption of innovation and the factors that influence the performance of the analysis was done by using SEM (Structural Equation Model). The results showed that the innovation of dried fish processing in Bengkulu City, which is the use of para-para tool and packaging, has the characteristics of relative advantages, compatibility, complexity, trialability, and good observability. Innovation has a low level of complexity by a simpler way of usage than others. Individual characteristics of dried fish artisans have a significant positive effect on the adoption of innovation. The largest contributing variable that reflects individual characteristics is training. The business characteristic variable does not affect the adoption of innovation because of the increasing characteristics of the business requirements, which demands better innovation from the current ones. The environmental drive variable has no significant effect on the adoption of innovation. Although high competition variables reflect environmental variables, competitors from outside the region have their own market share. Government support variables have a significant positive effect on the adoption of innovation. The adoption of innovation has a significant effect on the performance of dried fish processing MSEs in Bengkulu City, where the para-para indicator has bigger contribution than the packaging and the productivity variable has a bigger effect than the sales in reflecting the performance variable of MSE’s dried fish processing in Bengkulu City. Keywords: characteristics of innovation, adoption of innovation, business performance, SEM, MSE